2014
DOI: 10.7705/biomedica.v34i2.1807
|View full text |Cite
|
Sign up to set email alerts
|

Adaptación de la escala de Penn State College al idioma español para medición de profesionalismo en estudiantes de medicina

Abstract: Introduction:Professionalism is a subject of interest in medical schools around the world. The use of a questionnaire could be useful to assess professionalism in Colombia. Objective: To adapt The Penn State University College of Medicine Professionalism Questionnaire as a culturally valid instrument in the Spanish language. Materials and methods: We followed recommendations from the IQOLA project and used forward and back translation with four independent translations, as well as a pilot evaluation and an eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
2
0
3
Order By: Relevance
“…The PSCOM Professionalism Questionnaire was also validated for Spanish and after the factor analysis, four new domains were found, namely patient care, ethical attitude, partnership and relationship with health systems 7 . In a recent study to assess the reliability of the PSCOM Professionalism Questionnaire for Pakistan, it showed that despite the sevenfactor solution found, it occurred with a factorial structure that was different from the one observed in the original instrument, as in the respect domain, which now has five items instead of two 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PSCOM Professionalism Questionnaire was also validated for Spanish and after the factor analysis, four new domains were found, namely patient care, ethical attitude, partnership and relationship with health systems 7 . In a recent study to assess the reliability of the PSCOM Professionalism Questionnaire for Pakistan, it showed that despite the sevenfactor solution found, it occurred with a factorial structure that was different from the one observed in the original instrument, as in the respect domain, which now has five items instead of two 8 .…”
Section: Discussionmentioning
confidence: 99%
“…The PSCOM Professionalism Questionnaire was validated for Colombia 7 , Pakistan 8 and Turkey 9 . To the best of our knowledge, the PSCOM Professionalism Questionnaire…”
Section: Introductionmentioning
confidence: 99%
“…Este proyecto fue aprobado por el Comité de Ética en Investigación de la Universidad de La Sabana. El instrumento PSCOM fue validado previamente y los detalles metodológicos fueron explicados en profundidad en otra publicación 10 . Básicamente, la escala se empleó en estudiantes mayores de edad de la Facultad de Medicina de la Universidad de La Sabana, desde el primero hasta el duodécimo semestre.…”
Section: Materiales Y Métodosunclassified
“…Previamente, Blackall, et al 9 , desarrollaron el instrumento The Penn State University College of Medicine (PSCOM) Professionalism Questionnaire, con base en los seis criterios establecidos por la American Board of Internal Medicine y lo evaluaron en 765 médicos y 392 estudiantes, con buena validez y confiabilidad. Posteriormente, Bustamante y Sanabria 10 adaptaron culturalmente la misma escala al español y la validaron, y obtuvieron resultados similares a los del instrumento original. Como el profesionalismo es un área de interés creciente en la educación médica, instrumentos como el PSCOM pueden ser útiles para medir las actitudes de los estudiantes ante el profesionalismo y los cambios que se sufren durante el pregrado en Colombia, donde esta área ha sido poco explorada.…”
Section: Introductionunclassified
“…Bu konuda dünyada ve özellikle ülkemizde çalışmalar bulunmaktadır (12). İspanya (13) ve Pakistan (14)'da mezuniyet öncesi eğitimde kullanılan ölçek, mezuniyet sonrası eğitimde bir çok uzmanlık alanında kullanılmıştır (15,16).…”
Section: Introductionunclassified